Business plan workbook: a step by step guidance / Azlin Shafinaz Arshad, Yasmin Kamall Khan and Zanariah Zainal Abidin - Arshad, Azlin Shafinaz; Kamall Khan, Yasmin; Zainal Abidin, Zanariah (UiTM Press, 2025)
Every new business starts with a great idea. Entrepreneurs have identified a business that is unique in the product or service that they are planning to offer, or they believe they see an opportunity where they can provide a product or service that is better, faster, or cheaper. Either way, entrepreneurs need to ask themselves some questions about their business idea just to make sure they realistically evaluate the potential of their business. This workbook is intended to help entrepreneurs prepare for their businesses and deals with an important phase of the start-up process. Entrepreneur must try to fulfil these five sections by addressing all the items that apply to their business. However, not all items apply to all businesses. If the entrepreneur finds it difficult to address several applicable items in the workbook sections, more research needs to be carried out.